International Protection System of The New Turkish Law: A Conceptual Analysis - Bozkurt, Süheyla Balkar (Border Crossing, 2018)
International protection is the fundamental concept of international refugee law. Turkey has adopted in April 2013 a new Law No. 6458 on Foreigners and International Protection (LFIP) which is effective as of April 11, 2014. The major reform brought by the LFIP is, undoubtedly, the introduction of the international protection concept in Turkish law for the first time. This article aims to focus on the different statuses under which international protection will be provided according to the LFIP and to evaluate this new law vis-à-vis the international protection system in general.